The Effectiveness of Bright Light Therapy on Depressive Symptoms in Older Adults with Nonseasonal Depression: A Systematic Review. (December 2016) - Huang, S.; Su, H.; Sung, H.
Abstract : Background: Bright light therapy has become a standard treatment for seasonal affective disorder, as researchers have demonstrated the efficacy of bright light therapy as a first-line treatment in seasonal affective disorder, but its status in depression without seasonal pattern is unclear. Moreover, there have been no systemic reviews to synthesize the effects of bright light therapy for older adults with nonseasonal depression. Objectives: This systematic review describes the current evidence related to the effectiveness of bright light therapy on depressive symptoms in older adults with nonseasonal depression. Methods: A review was undertaken by searching English and Chinese electronic databases with specified search terms for the period of 2000–2015. PubMed, CINAHL, EMBASE, PsychInfo, Cochrane Central Trials, clinical trials.gov, and current controlled trials databases were searched. The search was limited to articles in the English and Chinese language and peer-reviewed journals. Two reviewers independently carried out study selection, data extraction and quality assessment using JBI appraisal tools. Results: Four research-based articles were included. All four study results showed that bright light therapy significantly reduced depressive symptoms of older adults with nonseasonal depression. Two studies used home-based individual light therapy, and the other two were conducted in the long-term care facilities. The dosages of the bright therapy were from 7500 lux to 10 000 lux, and the duration was from 30 to 60 minutes daily. Conclusion: This review concludes that bright light therapy had beneficial effects in older adults with nonseasonal depression. However, the evidence of the effect of bright light therapy for older adults with nonseasonal depression is not strong due to some methodological limitations in the reviewed studies. There is a need for further research using more rigorous research designs with a larger number of samples.